The Use of Collocations as a Measure of Translation Quality and Translator Competence - Bzour, Reham Zafer (2006)
A Master of Arts Thesis in English / Arabic / English Translation and Interpreting by Reham Zafer Bzour Entitled, "The Use of Collocations as a Measure of Translation Quality and Translator Competence," April 2006. Thesis Advisor is Dr. Basil Hatim. Available are both Soft and Hard Copies of the Thesis.